Violência contra mulheres brasileiras: estimação de subnotificações e impacto da COVID-19 sobre estupros, lesões corporais e feminicídios - Cunha, Pedro Milreu (2022)
The purpose of the presente dissertation was to verify the existence of a causal relationship between the COVID-19 pandemic (and its consequences) and violence against women in Brazil, in addition to quantifying this impact. For that, the methodology of analysis of structural breaks was used, in particular the techniques of binary segmentation and monitoring. In addition, the level of underreporting of crimes of rape and bodily harm against women for brazilian states was also estimated through the technique of stochastic boundary analysis. The results found indicate a high level of underreporting of crimes of rape against women, with an average underreporting of 33.54% for the entire sample; in addition, it was possible to verify a great heterogeneity in the distribution of underreporting values for the different brazilian states. For crimes of bodily harm against women, as expected, a lower average value was obtained, 1.30%. Regarding structural breaks, there is a clear effect of the COVID-19 pandemic on the crimes analyzed. While the average impact on rapes and femicides was positive, that is, the pandemic increased the occurrence of these crimes, for bodily harm the effect was the opposite. In all cases, not considering the effect of underreporting on results generated biased estimates of the impact of interest.